A Review On Addition Of ZINC Dialkyldithiophosphate In Vegetable Oil As Physical Properties Improver - Azhari, Muhamad Azwar; Fathe’li, Muhammad Asyraf; Aziz, Nur Syawal Aidill; Mohd Nadzri, Muhammad Syahir; Yusuf, Yusliza (Asian Research Publishing Network (ARPN), 2015)
-